2016
DOI: 10.1108/aeat-02-2015-0067
|View full text |Cite
|
Sign up to set email alerts
|

Compliant structures-based wing and wingtip morphing devices

Abstract: Purpose The purpose of this paper is to provide an overview of the design and experimental work of compliant wing and wingtip morphing devices conducted within the EU FP7 project NOVEMOR and to demonstrate that the optimization tools developed can be used to synthesize compliant morphing devices. Design/methodology/approach The compliant morphing devices were “designed-through-optimization”, with the optimization algorithms including Simplex optimization for composite compliant skin design, aerodynamic shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Wing level Maute and Reich 21 Material-based topology optimization 12.3 2.1 Simulation Vasista et al 29 Load-path topology optimization method 10.1 À6.8 /þ8.0 Wing level Smart Droop Nose 26 Traditional rigid-body mechanisms 20 -Wing level DARPA 51 Eccentuator and piezomotor-based actuation -+20…”
Section: Aerodynamic Analysis Of Leading-edge Deflectionmentioning
confidence: 99%
“…Wing level Maute and Reich 21 Material-based topology optimization 12.3 2.1 Simulation Vasista et al 29 Load-path topology optimization method 10.1 À6.8 /þ8.0 Wing level Smart Droop Nose 26 Traditional rigid-body mechanisms 20 -Wing level DARPA 51 Eccentuator and piezomotor-based actuation -+20…”
Section: Aerodynamic Analysis Of Leading-edge Deflectionmentioning
confidence: 99%
“…The model was designed and tested at Politecnico di Milano during the final part of NOVEMOR project which is one of the many projects promoted by the 7th European Framework Programme. Starting from the so called Reference Aircraft (RA), developed inside NOVEMOR project for the regional aviation segment, and used as a benchmark in order to evaluate the potential benefits that morphing devices can bring in terms of global performances [20], a small scale wing has been derived for the experimental validation of the proposed morphing concept [21].…”
Section: Design Manufacturing and Wind Tunnel Test Of A Morphing Winmentioning
confidence: 99%
“…The structural design chain starts with the skin design and the results at the end of this stage are transferred to the design domains of the compliant mechanisms which are designed via gradient-based topology optimization. The processes are briefly explained here and the reader is referred to Vasista et al 6 for more details.…”
Section: Structural Design Chain and Optimization Toolsmentioning
confidence: 99%
“…However, finite element analysis results of the structure under design flight loads (to be reported at a later stage) showed that the strains due to flight-aerodynamic loads still remained low. The reason for this imbalance may be attributed to the topology optimization problem formulation, which as presented in Vasista et al 6 was to maximize stiffness in the clean configuration subject to the shape control displacement constraints of the droop configuration. A problem formulation based on strain energy may lead to a better stiffness-flexibility balance.…”
Section: Topology Optimization Developmentsmentioning
confidence: 99%